Collective Individuality: Dante’s Moral Philosophical and Psychological Message in Paradise XXXI - Balducci, Marino Alberto (Ruch Filozoficzny, 2024)
This is a philosophical-moral study on the concept of altruistic happiness, through a hermeneutic analysis of a fundamental episode of the Divine Comedy. The symbol of the White Rose, contemplated by Dante in Paradise XXXI, represents the communion of saints, that is, of those who can experience in their psyche the extinction of desire in full joy. The kingdom of heaven is seen by the pilgrim poet as a beautiful flower with many petals. Its value is in the whole, the flower, but also in its individual parts, the petals. The salvation of the soul is therefore linked to altruism, to denying ourselves for our neighbors, in the name of a collective good. However, the poet shows us that every human individuality is precious, and the paradisiacal abolition of egoism is not the destruction of the uniqueness of the soul but the fulfillment of the self. Inside hell, which is described by Dante like an emblem of selfishness, Beatrice appears as a divine creature, ready to save her beloved poet. This means that Christianity starts the process of human salvation from the lowest material depth of the universe. Consequently, the low is not the opposite of the high: since there is also a high within that low. The individual, if purified from selfishness, becomes in the kingdom of heaven the independent and complementary mirror of a universal joy, a collective joy. Dante, deeply linked to Franciscanism, defends the Mariological concept of ‘Immaculate Conception’ and, in the Divine Comedy, offers us a philosophical-moral message that translates the profound meaning of this same theological idea into secular terms. The solitude of the individual matter that forms the body of every man is only apparent. We are not alone. There is another invisible, silent, very pure reality that has sunk into this matter of ours and into consciousness. This reality can save mankind and bring every person back into joyful wholeness.